Ukrainian Diaspora: A Journey of Traumatization, Resilience and Hope - Kölbel, Martin (Advances in Social Sciences Research Journal, 2023)
This study examines the influx of Ukrainian refugees into various European countries in the aftermath of the Russian attack. The author provides a comprehensive analysis of the multifaceted challenges faced by the refugees in three different receiving nations (i.e. Austria, England and Germany) through qualitative interviews and content analysis. The study also delves into the socio-economic, educational, and especially psychological aspects including traumatization and applied coping strategies of refugees to overcome negative experiences. The analysis revealed that huge differences in terms of traumatization as well as coping strategies to overcome experienced traumata could be observed among Ukrainian war refugees. For instance, language courses offered both within and outside educational facilities help war refugees to surmount language difficulties. Among other coping strategies to overcome experienced traumata, refugees connect with each other in the receiving countries to tackle past and present mental problems caused by family members fighting at war and insecure future perspectives.